Synthesis and Characterization of Co(II), Ni(II) and Cu(II) Complexes of Bidentate Schiff Base - VIDYARTHI, S.N.; KUMAR, DUSHYANT; SINGH, RAKESH; TIWARI, SHASHIKIRAN (Asian Journal of Chemistry, 2010)
In present studies, Co(II), Ni(II) and Cu(II) complexes with bidentate Schiff base have been prepared and characterized. The complexes were coloured, amorphous in nature and are soluble in DMSO and DMF. The conductance measurement shows the complexes are non-electrolytes in DMF. Elemental analysis confirmed to the 1:2 stoichiometry. Magnetic, electronic and IR spectral information suggest the octahedral structure for Co(II), Ni(II) and Cu(II) complexes.